Assessment of nutritional status of hemodialysis patients Hemodialysis Center SERSALUD Amazon E.I.R.L. Iquitos, 2016 - Becerra Ortiz, Mercy Lizeth (2019)
Objective: To assess the nutritional status of patients on hemodialysis. Methodology: quantitative approach, nonexperimental, cross-sectional and descriptive. The sample consisted of 100 patients between the ages of 20-80years, 60% were men and 40% women. instruments Subjective Global Assessment (SGA), Global AssessmentObjective (VGO) and 24-hour recall was used. Results: By body mass index, 54% normal and 19% mild andmoderate malnutrition. Regarding arm circumference (CB), 93% is appropriate. By muscular arm circumference(CMB), 45% is adequate protein reserve. The triceps skinfold (PTC), 27% in adequate caloric reserve, with mildand moderate malnutrition 27% and 24%, respectively. By serum albumin, 76% with mild malnutrition. Serumtransferrin, 60% had moderate malnutrition, and total lymphocyte count, 32% in mild malnutrition. 19% showedslight signs of ascites or edema. And as for 24-hour recall, 47% had moderate malnutrition protein intake, 96%are unsuitable for caloric intake. Conclusions: By the VGS found that 99% have mild malnutrition, while 25%moderate and 75% mild malnutrition according VGO.